ANALISIS TUTUPAN LAHAN DAN PERUBAHAN TUTUPAN LAHAN HUTAN DI DAERAH ALIRAN SUNGAI TENIHAWU KABUPATEN SABU RAIJUA - Febriyanti Monica Edo; Norman P.L.B. Riwu Kaho; Ludji Michael Riwu Kaho (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2019)
The purpose of this study was to determine land cover, land cover change and forest cover density in the Tenihawu river basin of Sabu Raijua Regency from 1998, 2008 and 2018. To find out what forest land cover is, you can use the Object method (OBIS / Object Based Image Segmentation)) and NDVI (Nomal Different Vegetation Index) to determine the density of forest land cover and tested using an error matrix. The data collected is primary data and secondary data. Primary data, namely Landsat-5 image material in 1999 and 2009, Landsat-8 image material in 2018 can be accessed via USG Glovis and secondary data from various library sources, documentation and from the publication of relevant agencies The results showed that the forest cover in the Tenihawu river basin amounted to 1101.02 Ha (36%) in 1.999, 862.77 Ha (28%) in 2009 and 683.78 Ha (22%) in 2018. Changes in forest cover in the Tenihawu basin will decrease from 1999 to 2009 by 238.25 Ha and from 2009 to 2018 by 178.99 Ha. The use of land in each village in the Tenihawu watershed are influenced by physiographic conditions and landforms, as it has a terrain structure and can have an impact on land use. False land use patterns can lead to critical land. The rapid development has led to changes in land use patterns, which space is increasingly dominated and nature spaces are being forced to change functions such as the conversion of land into paddy fields, plantations and settlements. The intrusion into the forest also leads to the loss of waste and humus, which can absorb rainwater. These events have a large scale that the behavior of the river are disturbed, while in the rainy season, the flow of the river significantly increases and the dry season, the flow of water is very low. In addition, the population is also a factor in changing land cover from a socio-economic point of view, namely the level of income of people around the forest, the needs and dependence of the population on forest products.